2017
DOI: 10.1002/adfm.201704507
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Achieved High Open‐Circuit Voltage and Efficient Charge Generation by Fine‐Tuning Charge‐Transfer Driving Force in Nonfullerene Polymer Solar Cells

Abstract: To maximize the short-circuit current density (J SC ) and the open circuit voltage (V OC ) simultaneously is a highly important but challenging issue in organic solar cells (OSCs). In this study, a benzotriazole-based p-type polymer (J61) and three benzotriazole-based nonfullerene small molecule acceptors (BTA1-3) are chosen to investigate the energetic driving force for the efficient charge transfer. The lowest unoccupied molecular orbital (LUMO) energy levels of small molecule acceptors can be fine-tuned by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
154
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 51 publications
6
154
0
1
Order By: Relevance
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…For homogeneous media, theory predicts a CT binding energy of around 400 meV, in clear contrast to the high external quantum efficiency (EQE) for photocurrent generation of many NFA‐containing devices. Several studies showed high EQE to be related to a larger driving force . This situation reminds of the “hot” dissociation model, where exciton dissociation creates a more loosely bound electronically/vibronically excited CT state .…”
mentioning
confidence: 72%
“…To determine the CT energy, we fitted the reduced EQE PV and EL spectra following the approach by Vandewal et al The resulting E CT = 1.41 eV is consistent with the value taken from the maximum of the derivative of the EQE PV curve, as also shown in Figure S4 (Supporting Information). Alternatively, we fitted only the low energy shoulder of the EL spectra using Marcus theory (as previously done in the work by Tang et al) which yields E CT = 1.29 eV. The singlet exciton energy of PM6 and Y6 were obtained from the crossing point of the absorption and photoluminescence (PL) spectra of the pristine films.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15] Key and fundamental strategies for designing high-effciency nonfullerene PSC devices are absorption spectrum and energy level. [18,19] In addition, the most difficult and complicated problem is how to precisely modulate the microstructure of the blending system. [16,17] The matching energy levels are crucial for donor and acceptor to ensure efficient driving force of exciton dissociation, to minimize voltage loss and thus to guarantee high V OC .…”
mentioning
confidence: 99%
“…Efficient charge separation is encouraged by having a small energetic offset (≈0.3 eV) between the LUMO of the ED and EA (Δ E LUMO in Figure a) and between HOMO of EA and ED (Δ E HOMO in Figure a). Conversely, some recent reports indicate that the HOMO/LUMO offset might not be necessary for FREA‐based OSCs and may also reduce charge transfer energy losses …”
Section: Osc Parameters and Architecturementioning
confidence: 94%